Design Computing and Cognition '18 - Gero, John S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the proceedings of the Eighth International Conference on Design Computing and Cognition (DCC'18) held at the Polytecnico di Milano in Italy. This volume presents both advances in theory and applications and demonstrates the depth and breadth of design computing and design cognition. Design thinking, the label given to the acts of designing, has become a paradigmatic view that has transcended the discipline of design and is now widely used in business and elsewhere. As a consequence there is an increasing interest in design research. This volume contains papers that represent the state-of-the-art research and developments in design computing and design cognition. This book is of particular interest to researchers, developers and users of advanced computation in design and those who need to gain a better understanding of designing that can be obtained through empirical studies. .
Preface -- List of Reviewers -- NEW DESIGN METHODS:Towards the Rapid Design of Engineered Systems Through Deep Neural Networks, by Christopher McComb -- Deep Componentbased Neural Network Energy Modelling for Early Design Stage Prediction, by Sundaravelpandian Singaravel and Philipp Geyer -- Unsuccessful External Search: Using Neuroimaging to Understand Fruitless Periods of Design Ideation Involving Inspirational Stimuli, by Kosa GoucherLambert, Jarrod Moss and Jonathan Cagan -- Designing With and For the Crowd: A Cognitive Study of Design Processes in NatureNet, by Stephen MacNeil, Sarah Abdellahi, Mary Lou Maher, Jin Goog Kim, Mohammad Mahzoon and Kazjon Grace -- A Comparison of Tree Search Method for Graph Topology Design Problems, by Ada Rhodes Short, Bryony Dupont and Matt Campbell -- DESIGN COGNITION - DESIGN APPROACHES: Externalizing Co-Design Cognition through Immersive Retrospection, byTomás Dorta, Emmanuel Beaudry Marchand and Davide Pierini -- Demystifying the Creative Qualities ofEvolving Actions in Design Reasoning Processes, by Tamir ElKhouly -- The Effect of Tangible Interaction on Spatial Design Tasks, by Jingoog Kim, Mary Maher and Lina Lee -- Sidebyside HumanComputer Design using a Tangible User Interface, by Matt Law, Nikhil Dhawan, Hyunseung Bang, SoYeon Yoon, Daniel Selva and Guy Hoffman -- DESIGN SYNTHESIS: Utility of Evolutionary Design in Architectural Form Finding: An Investigation into Constraint Handling Strategies, by Likai Wang, Patrick Janssen and Guohua Ji -- Exploring the Feature Space to Aid Learning in Design Space Exploration, by Hyunseung Bang, Lily Shi, SoYeon Yoon, Guy Hoffman and Daniel Selva -- Redefining Supports: Extending Mass Customization with Digital Tools for Collaborative Residential Design, by Tian Tian Lo, Basem Eid Mohamed and Marc Aurel Schnabel -- Voxel Synthesis for Generative Design, by Matvey Khokhlov, Immanuel Koh and Jeffrey Huang -- DESIGN THEORY: Model based abduction in designs, by Lauri Koskela and Ehud Kroll -- Ekphrasis as a Basis for a Framework for Creative Design Processes, by Udo Kannengiesser and John Gero -- Notes for an Improvisational Specification of Design Spaces, by Alexandros Charidis -- Design of Transfer Reinforcement Learning Mechanisms for Autonomous Collision Avoidance, by Xiongqing Liu and Yan Jin -- DESIGN COGNITION - DESIGN BEHAVIORS: Building a Social-Cognitive Framework for Design: Personality and Design Self-Efficacy Effects on Pro-Design Behaviors, by Hristina Milojevic and Yan Jin -- Cognitive Style and Field Knowledge in Complex Design Problem Solving: A Comparative Case Study of Decision Support Systems, by Yuan Ling Zi Shi, Hyunseung Bang, Guy Hoffman, Daniel Selva and SoYeon Yoon -- What Do Experienced Practitioners Discuss When Designing Product/Service Systems?, by Abhijna Neramballi, Tomohiko Sakao and John Gero -- Visual behaviour during perception of architectural drawings: differences between architects and non-architects, by Luis Vasconcelos, ChihChun Canan Colaco andCengiz Acarturk -- DESIGN GRAMMARS: On John Portman's Atria: Two Exercises in Hotel Composition, by Heather Ligler and Athanassios Economou -- Monitoring China's City Expansion in the UrbanRural Fringe: A Generative Grammar for Binjiang District in Hangzhou, by Ruichen Ni and Jose Duarte -- Composite Shape Rules, by Rudi Stouffs and Dan Hou -- Shape Grammars as a Probabilistic Model for Building Type Definition and Computation of Possible Instances: The Case Study of Ancient Greek and Roman Libraries, by Myrsini Mamoli -- Grammars for Making Revisited, by Djordje Krstic -- DESIGN PROCESSES: Rule-based systems in adaptation processes: a methodological framework for the adaptation of office buildings into housing, by Camilla Guerritore and Jose Duarte -- Using Argumentative, Semantic Grammar for Capture of Design Rationale, by Raymond McCall -- Identifying Design Rationale Using Ant Colony Optimization, by Miriam Lester and Janet Burge -- Biased Decision Making in Realistic ExtraProcedural Nuclear Control Room Scenarios, by Emil Andersen, Igor Kozine and Anja Maier -- DESIGN MODELLING: Modelling Collaboration in Parameter Design using Multiagent Learning, by Daniel Hulse, Kagan Tumer, Christopher Hoyle and Irem Tumer -- Exploring the Effect of Experience on Team Behaviour: A Computational Approach, by Marija Majda Perisic, Mario Storga and John Gero -- An Exploration of the Effects of Managerial Intervention on Engineering Design Team Performance, by Joshua Gyory, Jonathan Cagan and Kenneth Kotovsky -- A Study in Function Modeling Preferences and its Variation with Designer Expertise and Product Types, by Xiaoyang Mao and Chiradeep Sen -- DESIGN AND VISUALIZATION: Information Visualisation for Project Management: Case Study of Bath Formula Student Project, by Nataliya Mogles, Lia Emanuel, Chris Snider, James Gopsill, Sian JoelEdgar, Kevin Robinson, Ben Hicks, David Jones and Linda Newnes -- A Visualisation Tool to Investigate the Interplay of External and Internal Processes, by MiaArdiati Tedjosaputro and Yi Teng Shih -- Visual Interactivity to Make Sense of Heterogeneous Streams of Design Activity Data, by Yasuhiro Yamamoto and Kumiyo Nakakoji -- Style-Oriented Evolutionary Design of Architectural Forms Directed by Aesthetic Measure, by Agnieszka Mars, Ewa Grabska, Grażyna Ślusarczyk and Barbara Strug -- Creative Sketching Apprentice: Supporting Conceptual Shifts in Sketch Ideation, by Pegah Karimi, Kazjon Grace, Nicholas Davis and Mary Lou Maher -- First Author Email Index -- Author Index.
Keywords: Engineering design; Artificial intelligence; Cognitive psychology; Engineering Design; Artificial Intelligence; Cognitive Psychology